(untitled) (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
Shielded Metal Arc Welding (SMAW) is a welding process that is widely used because of its simplicity, versatility, and cost-effectiveness. However, in the process, there is a lot of wasted energy, reducing the benefits of the existing energy source, namely electricity. Increasing environmental pollution causes carbon emissions to increase. This study tested the results of SMAW welding against Stainless Steel 304 material by varying it into two factors and three levels. Stainless Steel 304 material is used because it is easy to obtain and is often applied in the industrial world. The types of testing are Visual Metalography and Destructive Test (DT). Observation results visual metalography show that the microstructure has changed in the welding area. While the DT used is the hardness test, and impact test. The DT test results experienced an increase in value, namely the hardness test and impact test. While the tensile test experienced a decrease in value. The factor that most effects visual metalography and DT is the Electric Current used.